Pemberdayaan Kader Posyandu melalui Transformasi Digitalisasi Layanan Kesehatan Masyarakat di Desa Karanganyar, Kecamatan Kedungbanteng, Kabupaten Tegal - Pebrian, Elpira; Amellia, Ananda Rizki; Azzahra, Lulu Fatimah; Fudholi, Muhammad Ilham; Rahman, Amanda Mutiara; Ghufron, Moh.; Alkautsar, Darma; Tandos, Rosita (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Posyandu cadre empowerment program in Karanganyar Village, Kedungbanteng District, Tegal Regency was implemented as an effort to improve the capacity of cadres in managing digital-based public health services. The background of this activity stems from the finding that the Posyandu activity recording and reporting system is still carried out manually, which often causes obstacles in terms of time efficiency, data accuracy, and coordination. Through a participatory approach, the activity was carried out by training cadres to use Google Forms, Google Spreadsheets, and WhatsApp channels as digital media for data collection, reporting, and communication of health information. The results of the activity showed an increase in the cadres' ability to manage health data digitally, strengthened basic digital literacy, and the formation of a more organized, faster, and secure recording system. This program not only encourages the transformation of Posyandu administration but also strengthens a professional and adaptive work culture among cadres in response to technological developments.